The Digital Divide in Philippine Litigation: A Phenomenological Study of Small-Firm Lawyers in the Province of Nueva Vizcaya Adapting to the Strategic Plan for Judicial Innovations (SPJI) 2022–2027 - Atty. Karpov B. Ablang; Atty. Katrina Bianca Inocentes (Future Science / FSH-PH Publications, 2026)
The Philippine judiciary has initiated technological reforms aimed at modernizing court administration and improving the efficiency and accessibility of judicial processes. Through the Strategic Plan for Judicial Innovations (SPJI) 2022–2027, the judiciary introduced initiatives such as electronic filing systems, digital case management platforms, and virtual hearings. While these reforms are intended to streamline litigation procedures and reduce administrative delays, concerns remain regarding the technological readiness of legal practitioners outside major urban centers. Provincial law offices often operate with limited access to reliable technological infrastructure, which may affect their ability to comply with emerging digital court requirements. This study examines how small-firm lawyers in the Province of Nueva Vizcaya experience and adapt to the ongoing digital transformation of litigation procedures. A qualitative phenomenological research design was employed to explore the lived experiences of practicing lawyers engaged in provincial litigation practice. Eighteen participants were selected through purposive sampling and interviewed using semi-structured interview protocols designed to capture their experiences with electronic filing systems, virtual hearings, and other technology-based judicial processes. Interview transcripts were analyzed through thematic interpretation using Colaizzi’s phenomenological method. The analysis revealed four central themes describing the digital divide in provincial litigation practice: constrained connectivity, negotiation of professional competence, adaptive strategies among practitioners, and uncertain expectations regarding the future of digital court systems. The findings suggest that digital judicial reforms create both opportunities and challenges for provincial practitioners and highlight the need for institutional support mechanisms that promote inclusive participation in emerging digital court systems.